1987
DOI: 10.1029/rs022i001p00037
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between the degree of preferred orientation in precipitation and dual‐polarization radar echo characteristics

Abstract: the paper "On the relationship between the curate. The second to last paragraph of section 7 of degree of preferred orientation in precipitation and the paper should be replaced by the following: dual-polarization radar echo characteristics" by A."It is seen throughout these results that the media Hendry, Y. M. M. Antar, and G. C. McCormick cannot be considered to be equioriented, i.e., the par-(Radio Science, 22(1), 37-50, 1987), incorrect values ticles do not all have a common alignment. The low for two of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…These deductions are in good agreement with the observations of the canting-angle distributions of raindrops using linear and circular polarisation measurements [6]. In this paper we assume that the raindrops are equi-oriented with the minor axis of the oblate spheroid being vertical [23].…”
Section: N Re F[jhh(d)-fvv(d)]n(d) Dd Kosupporting
confidence: 74%
See 1 more Smart Citation
“…These deductions are in good agreement with the observations of the canting-angle distributions of raindrops using linear and circular polarisation measurements [6]. In this paper we assume that the raindrops are equi-oriented with the minor axis of the oblate spheroid being vertical [23].…”
Section: N Re F[jhh(d)-fvv(d)]n(d) Dd Kosupporting
confidence: 74%
“…The pioneering studies of McCormick, Hendry and their associates at the National Research Council of Canada have established the basis of polarimetric techniques, both for backscatter as well as forward scatter (propagation), using circular polarisation [3][4][5][6]. They have reported measurements of differential attenuaton and differential phase shift in rain at K-, Xand S-hands, using the range profile of W /W 2 were W is the complex crosscovariance between the co-and crosspolar (simultaneously) received signals and W 2 is the conventional reflectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The main assumptions are : (a) The attenuation and reflection are calculated for spherical particles using Mie theory. Measurements with polarisation radar (Hall et al [7], Hendry et al [8]) clearly show horizontal flattening of the particles towards the end of melting and this phenomenon could be included in the model when the shape and angle distributions of these particles are better known.…”
Section: The Melting Layer Modelmentioning
confidence: 99%
“…Our modeling results also showed that it is possible to separate orientation effects from shape effects as was suggested by [28]. This is done by calculating LDR (linear depolarization ratio) in the characteristic polarization basis and also in the linear basis 45°in tilt angle from the characteristic polarization basis.…”
Section: Comparison Of Voltage Equationsmentioning
confidence: 94%
“…In order to separate particle shape effects from the effects of orientation (i.e., spread of canting angle distribution) a technique suggested by [28] is used. They showed that the ratio of the maximum to minimum LDR value for linear polarizations is nearly independent of shape effects and depends primarily on orientation effects.…”
Section: B Separation Of Shape and Orientationmentioning
confidence: 99%